Workers without borders : posted work and precarity in the EU - Wagner, Ines, 1984- (ILR Press, an imprint of Cornell University Press, 2018)
"Analyzes EU posted work in theory and practice from the point of view of the posted worker and identifies emerging structures of access and denial to labor rights for temporary intra-EU migrant workers based on extensive qualitative data collection in Germany"--